Language Learning Strategy Use across Gender - Sri Wahyuni (JLA (Jurnal Lingua Applicata), 2022)
This study examines the effects of gender on Indonesian EFL tertiary students’ use of learning strategies for speaking skills. It addresses what learning strategies the students use, what strategy and strategy group they favour, and whether gender significantly affects the strategy use. This paper reports the quantitative part of a larger mixed method study which draws on questionnaire (N= 65) obtained at Gajayana University of Malang. The study demonstrates that the students used a wide range of strategies that spread over six strategy groups. Male students favoured the strategy ‘finding out about language learning’ and the strategy group of ‘compensation’. Female students favoured the strategy ‘paying attention’ and the strategy group of ‘metacognitive’. The study also shows that gender significantly affected the use of ‘affective’ strategies only. The paper concludes by discussing implications for theory and practice.